Application of simple and effective thermal switch for solid-state magnetic refrigeration at room temperature. (5th June 2019) - Utaka, Yoshio; Hu, Kang; Chen, Zhihao; Zhao, Yanjie
Abstract: Solid-state magnetic refrigeration systems that operate near room temperature have been proposed and studied in recent years because of their potential to improve system performance. Most solid-state MR systems require a thermal switch to control the heat transport; however, the thermal switches proposed to date are of limited applicability because of their complicated structures, low thermal conductivity, low durability, and high cost. Therefore, this study investigated an alternative type of thermal switch that is much easier to implement in practical solid-state MR systems, and the performance of the proposed thermal switch was validated by numerical simulation. The results showed that the proposed thermal switch is effective in the solid-state magnetic refrigeration system. Moreover, increasing the number of unit elements effectively improves the system performance. For the solid-state magnetic refrigeration system with certain number of unit elements, the operating frequency can also be optimized to achieve the best performance. In addition, the system performance could be further improved by utilizing a magnetocaloric material with increased thermal conductivity.